2021
DOI: 10.14202/vetworld.2021.1234-1240
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol extract from Moringa oleifera leaves modulates brown adipose tissue and bone morphogenetic protein 7 in high-fat diet mice

Abstract: Background and Aim: Brown adipose tissue's (BAT) ability to increase energy expenditure has become a new focus in obesity research. The amount and activity of BAT are inversely correlated with body-mass index and body fat percentage. Bone morphogenetic protein 7 (BMP7) plays a role in the differentiation and development of BAT, which can be increased by bioactive compounds from several medicinal plants. Moringa oleifera (MO) leaves are rich with vitamin, minerals, and bioactive compounds and have been used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…In recent years, some studies have shown that extracts from M. oliefera leaves could regulate lipid metabolism. For example, Syamsunarno et al ( 43 ) explored the effects of ethanol extract from M. oleifera leaves on modulating brown adipose tissue differentiation in mice fed an HFD. Mabrouki et al ( 44 ) evaluated the effect of the methanolic extract of M. oleifera leaves on HFD-induced obesity and cardiac damage in rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, some studies have shown that extracts from M. oliefera leaves could regulate lipid metabolism. For example, Syamsunarno et al ( 43 ) explored the effects of ethanol extract from M. oleifera leaves on modulating brown adipose tissue differentiation in mice fed an HFD. Mabrouki et al ( 44 ) evaluated the effect of the methanolic extract of M. oleifera leaves on HFD-induced obesity and cardiac damage in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Our team has also investigated M. oleifera leaf petroleum ether extract inhibits lipogenesis ( 46 ). In these studies, the main components of M. oleifera leaf extracts were phenolic compounds ( 44 ) and flavonoid glycosides ( 46 ), without even elucidating their main components ( 43 , 45 ). Therefore, the activity of MOP in regulating lipid metabolism is currently unclear.…”
Section: Discussionmentioning
confidence: 99%
“…This study suggested that flavonoids found in MO could modulate the BMP7 expression. However, this study did not provide phytochemical analysis, but they proposed that flavonoids were responsible for the mechanisms ( Syamsunarno et al, 2021 ). These data were supported by an in vitro study that used human adipose-derived mesenchymal stem cells to investigate the effect of MO on lipids metabolism and antioxidant systems related to the adipogenesis process ( Barbagallo et al, 2016 ).…”
Section: Role Of Mo In Cardiovascular Diseasesmentioning
confidence: 87%
“…MO is traditionally consumed in raw materials, such as fresh leaves or leaves powder, manufactured commercially by the community ( Syamsunarno et al, 2021 ). These preparations are also applied in various human studies and become a challenge in implementing studies that use oral administration methods due to the unpleasant odor and intolerable taste of MO leaves.…”
Section: Limitations and Recommendation For Future Researchmentioning
confidence: 99%
“…Coagulant protein isolated from MO possessed a great antimicrobial action against many isolates of bacteria isolated from water [195]. Leaf extract could modulate the diferentiation of brown adipose tissue through the upregulation of bone morphogenetic protein 7 (BMP7) levels in obese mice [196]. Te ethanolic extracts were associated with signifcant normalization of proteins of antioxidant, antiinfammatory, and antiapoptotic activities [197].…”
Section: Moringa Oleifera and Proteinsmentioning
confidence: 99%